Genetic Associations With Gestational Duration and Spontaneous Preterm Birth. Issue 2 (February 2018) - Zhang, Ge; Feenstra, Bjarke; Bacelis, Jonas; Liu, Xueping; Muglia, Lisa M.; Juodakis, Julius; Miller, Daniel E.; Litterman, Nadia; Jiang, Pan-Pan; Russell, Laura; Hinds, David A.; Hu, Youna; et al.
Abstract : (Abstracted from N Engl J Med 2017;377:1156–1167) Preterm birth, caused by idiopathic onset of uterine contractions or rupture of fetal membranes, is a major risk factor for death in neonates and children younger than 5 years. Although there is evidence that preterm birth and gestational duration are affected by both maternal and fetal genomes, robust associations with genetic variations are still not established.